Management of a large spontaneously ruptured dermoid cyst: a case report from large tertiary hospital in Australia - Pandey, Santvana; Mukundan, Manju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Mature cystic teratomas (MCT), more commonly known as dermoid cysts (DC), are the most common type of ovarian growth, a type of germ cell tumor. MCT are typically small and not prone to spontaneous ruptures, we present a case of a large MCT which had spontaneous rupture. This is a case of 37-year-old nulligravida, with no medical history who presented to emergency department because of abdominal pain. She was admitted, diagnosis and radiographical findings plus the clinical examination led to identification of large pelvic mass, with possible DC, and due to associated pain was undertaken for surgery.